Welcome to Westonci.ca, your one-stop destination for finding answers to all your questions. Join our expert community now! Get immediate and reliable answers to your questions from a community of experienced professionals on our platform. Experience the convenience of finding accurate answers to your questions from knowledgeable experts on our platform.
Sagot :
Step-by-step explanation:
proof from r.h.s to l.h.s
(cot(a)-tan(a))(cot(a)+tan(a))
cot(a)=cos(a)/sin(a)
tan(a)=sin(a)/cos(a)
(cot(a)-tan(a))=cos(a)/sin(a) - sin(a)/cos(a)
=cos²(a)-sin²(a)/sin(a)cos(a)
from trigonometry identity cos²(a)-sin²(a)=cos2(a)
so we have cos2(a)/sin(a)cos(a)
(cot(a)+tan(a))=cos(a)/sin(a) +sin(a)/cos(a)
=cos²(a)+sin²(a)/cos(a)sin(a)
from trigonometry identity cos²(a)+sin²(a)=so we have 1/cos(a)sin(a)
(cot(a)-tan(a)) ÷(cot(a)+tan(a))
=cos2(a)/cos(a)sin(a) ÷ 1/cos(a)sin(a)
=cos2(a)/cos(a)sin(a) * cos(a)sin(a)
=cos2(a)
proved
Thank you for visiting our platform. We hope you found the answers you were looking for. Come back anytime you need more information. Thanks for stopping by. We strive to provide the best answers for all your questions. See you again soon. Thank you for visiting Westonci.ca, your go-to source for reliable answers. Come back soon for more expert insights.